STATISTICAL ASSESSMENT OF THE FORMATION AND DEVELOPMENT PATHS OF THE EDUCATIONAL SERVICES MARKET IN THE REGIONS - Astanayev Kulmakhammat Sanayevich (Ecominds Press, 2026)
This study examines the formation and development trends of the educational services market in Uzbekistan for 2014–2024. Using statistical analysis of population, student enrollment, teaching staff, and wages, the research identifies key growth dynamics. Results show rapid expansion of student numbers, slower growth of teachers, and rising wages, which increased financial incentives but also intensified workload pressure. The worsening teacher–student ratio signals risks for education quality. The study concludes that sustainable market development requires expanding teaching capacity, digital solutions, and closer state–private cooperation.
Keywords: Educational services market, human capital, higher education, statistical analysis, time series, supply and demand, teacher–student ratio, economic efficiency, state policy, competitiveness.